Cranioplasty with Adipose‐Derived Stem Cells, Beta‐Tricalcium Phosphate Granules and Supporting Mesh: Six‐Year Clinical Follow‐Up Results. (15th May 2017) - Thesleff, Tuomo; Lehtimäki, Kai; Niskakangas, Tero; Huovinen, Sanna; Mannerström, Bettina; Miettinen, Susanna; Seppänen‐Kaijansinkko, Riitta; Öhman, Juha
Abstract: Several alternative techniques exist to reconstruct skull defects. The complication rate of the cranioplasty procedure is high and the search for optimal materials and techniques continues. To report long‐term results of patients who have received a cranioplasty using autologous adipose‐derived stem cells (ASCs) seeded on beta‐tricalcium phosphate (betaTCP) granules. Between 10/2008 and 3/2010, five cranioplasties were performed (four females, one male; average age 62.0 years) using ASCs, betaTCP granules and titanium or resorbable meshes. The average defect size was 8.1 × 6.7 cm 2 . Patients were followed both clinically and radiologically. The initial results were promising, with no serious complications. Nevertheless, in the long‐term follow‐up, three of the five patients were re‐operated due to graft related problems. Two patients showed marked resorption of the graft, which led to revision surgery. One patient developed a late infection (7.3 years post‐operative) that required revision surgery and removal of the graft. One patient had a successfully ossified graft, but was re‐operated due to recurrence of the meningioma 2.2 years post‐operatively. One patient had an uneventful clinical follow‐up, and the cosmetic result is satisfactory, even though skull x‐rays show hypodensity in the borders of the graft. Albeit no serious adverse events occurred, the 6‐year follow‐up results of the five cases are unsatisfactory. The clinical results are not superior to results achieved by conventional cranial repair methods. The use of stem cells in combination with betaTCP granules and supporting meshes in cranial defect reconstruction need to be studied further before continuing with clinical trials. Stem Cells Translational Medicine 2017;6:1576–1582 Abstract : Reformatted CT image 13 months after reconstruction of the skull with autologous adipose stem cells, beta‐tricalcium phosphate granules and supporting mesh.